Safety and Feasibility of Augmented Reality Assistance in Minimally Invasive and Open Resection of Benign Intradural Extramedullary Tumors - Fabian Sommer; Ibrahim Hussain; Sertac Kirnaz; Jacob Goldberg; Lynn McGrath; Rodrigo Navarro-Ramirez; Francois Waterkeyn; Franziska Schmidt; Pravesh Shankar Gadjradj; Roger Härtl (Neurospine, 2022)
Objective Surgical resection of benign intradural extramedullary tumors (BIETs) is effective for appropriately selected patients. Minimally invasive surgical (MIS) techniques have been described for successful resection of BIET while minimizing soft tissue injury. Augmented reality (AR) is a promising new technology that can accurately allow for intraoperative localization from skin through the intradural compartment. We present a case series evaluating the timing, steps, and accuracy at which this technology is able to enhance BIET resection. Methods A protocol for MIS and open AR-guided BIET resection was developed and applied to determine the feasibility. The tumor is marked on diagnostic magnetic resonance imaging (MRI) using AR software. Intraoperatively, the planning MRI is fused with the intraoperative computed tomography. The position and size of the tumor is projected into the surgical microscope and directly into the surgeon's field of view. Intraoperative orientation is performed exclusively via navigation and AR projection. Demographic and perioperative factors were collected. Results Eight patients were enrolled. The average operative time for MIS cases was 128 ±8 minutes and for open cases 206 ±55 minutes. The estimated intraoperative blood loss was 97 ±77 mL in MIS and 240 ±206 mL in open procedures. AR tumor location and margins were considered sufficiently precise by the surgeon in every case. Neither correction of the approach trajectory nor ultrasound assistance to localize the tumor were necessary in any case. No intraoperative complications were observed. Conclusion Current findings suggest that AR may be a feasible technique for tumor localization in the MIS and open resection of benign spinal extramedullary tumors.